Association of Incidences of Burns and Place of Occurrence - Investigative Approach among Victims of Domestic Violence - Zulfiqar Ali Buzdar, Nassir Nazir, Mansoora Mirza (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Burn injuries are the trauma to live human tissue as result of some burning source including fire, flame, heat, electricity or some chemical. The interrelated intricate complexity of the place of occurrence and incidents of burns had long been a scope of interest to medical and medicolegal personnel. Aim: To investigate the association of incidences of burns with their place of occurrence. Methodology: The research data has been collected from the victims of domestic burn presenting in the Accident and Emergency Department (AED) Jinnah Hospital Lahore and filtered at the medicolegal clinic of Alama Iqbal Medical College Lahore. A total of 250 burns of domestic violence were registered from January 2018 to August 2018 and were included in the study after fulfilling the exclusion and exclusion criteria. Observation research method was carried out with descriptive cross-sectional study design by applying quantitative questionnaire as a data collection tool. The study population consisted of the rural and urban areas of the area of drainage of the said research settings. Results: The study revealed highly significant association with medium of burns and place of occurrence grossly taking place at home with scalds as most frequent medium with 0.000 significant p value. Single or unmarried population was strongly associated with p value 0.004 facing burn injuries at home. Professional population versus amateur had also shown strong association for place of occurrence as home for burn injuries with p value 0.021 though less marked in professional population. The study concludes that scalds as commonest medium, single unmarried persons involved more than married ones and home of the victim was an easy target for the perpetrators. Conclusion: The study revealed strong association of medium of burns, marital status and proficiency of the population for incidence of burns frequently had home setting as a place of occurrence. Keywords: Burns, Domestic Violence, Place of Occurrence, Incidences of Burns